Implementing the Jam’iyyah Mudarasatil Qur’an Lil Ḥāfiẓāt Program to Enhance Motivation and Qur’anic Memorization Quality - Kholidatuzzuhriyah Kholidatuzzuhriyah; Jasminto Jasminto; Khoirotul Idawati; Asriana Kibtiyah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to examine the implementation of the Jam’iyyah Mudarasatil Qur’an Lil Ḥāfiẓāt (JMQH) program in enhancing motivation and the quality of Qur’anic memorization among female memorizers (ḥāfiẓāt) in Jombang District. A qualitative research approach with a case study design was employed. Data were collected through in-depth interviews, participant observation, and documentation involving JMQH administrators and active members. Data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing, supported by source and technique triangulation to ensure data credibility. The findings indicate that the JMQH program is implemented through well-structured routine activities, including monthly mudarasah, tartil-based recitation, peer listening (simāʿ), and spiritual development sessions conducted alternately at members’ residences. The program significantly enhances members’ motivation by fostering peer support, collective commitment, and a supportive religious environment. Furthermore, improvements in memorization quality are evident in increased fluency, accuracy, and adherence to tajwīd rules. Key supporting factors include strong religious awareness, a sense of community belonging, and a positive social environment, while inhibiting factors involve domestic responsibilities and initial feelings of insecurity. This study concludes that community-based religious organizations such as JMQH play a vital role in sustaining Qur’anic memorization among adult female memorizers beyond formal educational institutions